Malaysian teachers’ perspectives on the challenges of low-income parents with special child - Abd Karim, Aishah Hanim; Salleh, Sharifah; Mohd Isa, Muhammad Ariffudin; Kassim, Siti Kholijah; Ismail, Nik Ahmad Hisham; Rais, Haniza (Fakulti Pengajian Pendidikan, Universiti Putra Malaysia Serdang, Selangor MALAYSIA., 2024)
The aim of the present study is to explore Malaysian teachers’ perspectives on the challenges faced by low-income parents in managing their special child. This qualitative study applied a case study method involving one male and one female teacher who possess more than three years working experience at early intervention centres located in the Klang Valley, Malaysia. They were interviewed individually using a semi-structured interview. The data were transcribed verbatim, translated into English, and then analyzed using thematic analysis approach. The themes generated on the challenges that are faced by low-income parents include financial resources, interventions, dealing with child’s behaviour, lack of support, and dealing with emotions. To conclude, teachers understood low-income parents’ challenges in managing their special child. They were ready to assist them by providing various support services at the early intervention centres that they were working at. This study provides insights for practitioners, counselors, teachers, and therapies to have empathy on parents who struggle to manage their special child on a daily basis. Future studies may include teachers working at early intervention centres located in other states and middle-to-high income parents as well.